2012
DOI: 10.4315/0362-028x.jfp-11-165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Most-Probable-Number–PCR Method with Internal Amplification Control for the Counting of Total and Pathogenic Vibrio parahaemolyticus in Frozen Shrimps

Abstract: The most-probable-number (MPN) method is often time-consuming for the isolation, detection, and quantification of Vibrio parahaemolyticus from natural sources. MPN counting of V. parahaemolyticus bacteria usually involves the isolation of typical V. parahaemolyticus colonies on selective medium, with subsequent confirmation by biochemical identification. In this study, we evaluated the use of a PCR on MPN enrichment cultures (MPN-PCR) for the direct detection of total and pathogenic V. parahaemolyticus cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…The most probable number coupled with polymerase chain reaction (MPN-PCR) method detailed in the literature was adapted for determining the total Vibrio spp. density (TVD) in water samples ( Ahmad et al, 2011 ; Copin et al, 2012 ; Ramos et al, 2014 ; Abioye and Okoh, 2018 ). As a statistical-based method, MPN only estimates the viable numbers of bacteria in a sample by the principle of extinction dilution, i.e., inoculating liquid medium in 10-fold dilutions to a dilution factor at which no turbidity is observed after the incubation period.…”
Section: Methodsmentioning
confidence: 99%
“…The most probable number coupled with polymerase chain reaction (MPN-PCR) method detailed in the literature was adapted for determining the total Vibrio spp. density (TVD) in water samples ( Ahmad et al, 2011 ; Copin et al, 2012 ; Ramos et al, 2014 ; Abioye and Okoh, 2018 ). As a statistical-based method, MPN only estimates the viable numbers of bacteria in a sample by the principle of extinction dilution, i.e., inoculating liquid medium in 10-fold dilutions to a dilution factor at which no turbidity is observed after the incubation period.…”
Section: Methodsmentioning
confidence: 99%
“…The classic method of identifying V. parahaemolyticus relies on a variety of biochemical tests, which are laborious and time‐consuming. Modern identification techniques especially based on molecular biology and immunology are developed . Besides, the development of analytical techniques for fatty acid (FA) has rendered use of fatty‐acid based technology to identify a number of organisms practically .…”
Section: Introductionmentioning
confidence: 99%
“…The LoDs of the LAMP assay revealed that LAMP reactions were not influenced by any inhibitor present in the prepared DNA template solutions from seafood and seawater, whereas PCR reactions were somewhat handicapped by inhibitors (Copin et al . ; Karanis et al . ).…”
Section: Resultsmentioning
confidence: 99%